Repositioning Blackness and Intersectional Identities in Adichie’s Americanah - Mulyani, A.B. Sri; Putri, Pangestin Aprilia Sehnur (Universitas Sanata Dharma, 2024)
This article scrutinizes Adichie’s Americanah to problematize the homogeneous concept of blackness and its related intersectional identities such as race, ethnicity, tribe, nationality, class, gender, language, and its relevant aspects. By employing the perspectives of women of color feminisms, particularly, on the world stage that pays a close attention to the global, postcolonial, and transnational feminisms, this article is able to locate at least two key points in Americanah to challenge the domination of the homogeneity and stereotype of blackness. Among the identified key points are the reflexivitive narrative style and the presence of the blog posts in the novel. The reflexivity enables the fluidity of inward and outward perceptions and assessments to examine and reexamine intersectional issues and experiences. Meanwhile, the blog posts in the form of writing about writing also provide fluid and open spaces for the polyvocality of diverse opinions and arguments regarding the intersectional realities. Accordingly, in such manner, the novel attempts to articulate the heterogeneity, specificity, and multiplicity of the so-called blackness and intersectional identities to challenge the myopic view of blackness and the complexity of entangled identities.